PENGGUNAAN TOKSIN BOTULINUMA DENGAN PANDUAN ULTRASONOGRAFI SEBAGAI TERAPI SINDROM PIRIFORMIS REKUREN SERIAL KASUS - Yusak Mangara Tua Siahaan (Neurona Majalah Kedokteran Neuro Sains, 2020)
SYNDROME PS IS A CLINICAL SYNDROME WITH COMPLAINTS OF BUTTOCK PAIN THAT RADIATES TO THE UNILATERAL SIDE LEG CAUSED BY SCIATIC NERVE ENTRAPMENT OF PIRIFORMIS MUSCLE SEVERAL THERAPY MODALITIES OF PS ARE ORAL PHYSICAL INTERVENTION AND SURGICAL THERAPY INTRAMUSCULAR INJECTION THERAPY IS AN INTERVENTION THERAPY FOR PATIENTS WHO EXPERIENCE SEVERE PAIN OR HAVE FAILED ORAL THERAPY ANDOR PHYSICAL THERAPY